Aislamiento y caracterización de bacterias carboxidótrofas potencialmente útiles en el desarrollo de un sensor enzimático para monóxido de carbono (2005)
This paper reports the isolation and characterization of 4 native strains from a wastewater treatment plant in the town of Ginebra, Valle del Cauca, Colombia, that were grown in a mineral environment saturated with Carbon Monoxide at 30ªC under constant agitation. Their behavior was compared to the Oligotropha carboxidovorans bacterium, OM 5 strain, acquired from the American Type Culture Collection (ATCC) and previously studied in the enzymatic construction for CO.